1998
DOI: 10.1111/j.1749-6632.1998.tb10584.x
|View full text |Cite
|
Sign up to set email alerts
|

Odorant‐Binding Proteins: Structural Aspects

Abstract: Structural data on odorant-binding proteins (OBPs), both in vertebrates and in insects, are reviewed and discussed. OBPs are soluble proteins interacting with odor molecules and pheromones in the perireceptor areas, the nasal mucus in vertebrates and the sensillar lymph in insects. The physiological function of these proteins is still uncertain, but information on their structure is abundant and accurate. Based on complete amino acid sequences, several subclasses have been identified, suggesting a role in odor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 81 publications
1
63
0
Order By: Relevance
“…The three-dimensional structures of honey bee OBPs are likely to be very similar as suggested by the alignment of the six ␣-helices characteristic of this class of proteins (Pelosi 1998). The six-cysteine signature found in the OBP family is conserved in 13 members with all the honey bee proteins having four conserved cysteines.…”
Section: Annotation Of the Honey Bee Genes Encoding Obp-like Proteinsmentioning
confidence: 80%
“…The three-dimensional structures of honey bee OBPs are likely to be very similar as suggested by the alignment of the six ␣-helices characteristic of this class of proteins (Pelosi 1998). The six-cysteine signature found in the OBP family is conserved in 13 members with all the honey bee proteins having four conserved cysteines.…”
Section: Annotation Of the Honey Bee Genes Encoding Obp-like Proteinsmentioning
confidence: 80%
“…Therefore, AlinOBP1 EST appears to contain the complete coding region. The predicted amino acid sequence of AllinOBP1 CDS has the typical six-cysteine signature of insect OBPs (Pelosi, 1998) with a signal peptide of 18 amino acid residues at the N terminus (Fig. 2).…”
Section: Cdna Sequence Analysismentioning
confidence: 99%
“…This odorant-binding protein was referred to as a pheromone-binding protein (PBP) (Vogt and Riddiford 1981). Subsequently, additional OBP sequences were identified in Lepidoptera (Györgyi et al 1988, Raming et al 1989 that showed differential expression pattern and distinct binding properties to different classes of odorant molecules (Krieger et al 1996, Pelosi 1998, Vogt and Lerner 1989, Vogt et al 1991a. Accordingly, insect OBPs are now classified into three groups: PBPs, general odorant-binding proteins (GOBPs) and antennal binding protein X (ABPX).…”
Section: Odorant-binding Proteinsmentioning
confidence: 99%